Developing and Validating a SMART-Based Writing Materials Framework for Pre-Service EFL Teachers - Yulandari, Evi Safitri; Muliadi, Mul (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Writing competence remains a critical yet challenging component of EFL teacher education, particularly in enabling pre-service teachers to design scaffolded, measurable, and genre-sensitive instructional objectives. Although the SMART framework (Specific, Measurable, Achievable, Relevant, and Time-bound) has been widely adopted in instructional planning, its systematic application and validation within writing pedagogy remain limited. Addressing this gap, the present study aimed to develop and validate a SMART-based instructional framework refined through the iterative Successive Approximation Model (SAM). Adopting a mixed-methods research and development (R&D) design, the study followed successive phases of preparation, design, development, implementation, and evaluation. The framework was validated by expert reviewers in language, material, and media, and subsequently trialed with fifth- and seventh-semester pre-service EFL teachers. Quantitative data were collected through validation instruments and competence assessments, while qualitative data were obtained from participant feedback, instructional artifacts, and reflective responses. Descriptive and inferential analyses indicated that the framework demonstrated strong content validity and instructional relevance, although aspects of practicality required further refinement. The iterative nature of SAM facilitated continuous improvement based on expert and user feedback, resulting in a more responsive and learner-centered design. The findings suggest that the SMART-based framework effectively enhances pre-service teachers’ competence in formulating instructional objectives for writing and functions as both a developmental and diagnostic tool in teacher education. This study contributes a praxis-oriented instructional framework that bridges theoretical rigor and classroom applicability, with implications for curriculum integration, genre-based scaffolding, and future development of technology-enhanced instructional supports.